2020
DOI: 10.1093/zoolinnean/zlaa052
|View full text |Cite
|
Sign up to set email alerts
|

First insights into the phylogeny of tok-tokkie beetles (Tenebrionidae: Molurina, Phanerotomeina) and examination of the status of thePsammodes vialisspecies-group

Abstract: The first molecular phylogeny of the tribe Sepidiini is inferred from analyses of DNA sequence data from the following five loci (CAD, wg, COI, COII, 28S rRNA). Bayesian and maximum likelihood analyses were performed on a dataset containing 41 taxa, of which a majority represent Molurina (27) and Phanerotomeina (6). The resulting topologies were used to discuss phylogenetic placement and diagnostic characters of all of the genera representing Molurina. Within the subtribe, the results revealed paraphyly of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 704 publications
(39 citation statements)
references
References 19 publications
2
37
0
Order By: Relevance
“…The present note is a direct continuation of my taxonomic studies on the tribe Sepidiini Eschscholtz, 1829 (Kamiński et al 2019, 2022 and in particular the recently published revision of the genus Toktokkus (Kamiński et al 2021. Up to now, I have investigated a diverse set of specimens concerning Toktokkus from several entomological collections around the world, including most of the type material (Kamiński et al 2021). During my recent visit to the Natural History Museum London (BMNH) I discovered a new species representing this genus and Angolan specimens significantly extending the distributional ranges of previously known species.…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…The present note is a direct continuation of my taxonomic studies on the tribe Sepidiini Eschscholtz, 1829 (Kamiński et al 2019, 2022 and in particular the recently published revision of the genus Toktokkus (Kamiński et al 2021. Up to now, I have investigated a diverse set of specimens concerning Toktokkus from several entomological collections around the world, including most of the type material (Kamiński et al 2021). During my recent visit to the Natural History Museum London (BMNH) I discovered a new species representing this genus and Angolan specimens significantly extending the distributional ranges of previously known species.…”
mentioning
confidence: 55%
“…Due to the presence of microtubercles on the elytra, relatively small body size (21.0 mm), and extremely finely punctate pronotal disc this new species is close to Toktokkus tuberculipennis (Haag-Rutenberg, 1871) (see Fig. 2D in Kamiński et al 2021). However, it can be sharply distinguished from that species, and all other congeners, by the presence of three distinctly elevated parallel rows on each elytron (Fig.…”
Section: Toktokkus Mariae Sp Novmentioning
confidence: 87%
See 1 more Smart Citation
“…Koch (Flores & Vidal, 2009) and Praocis (Praocis) Eschscholtz (Flores & Pizarro-Araya, 2012). Conversely, in a recent study of the African representatives of the Pimeliinae, tribe Sepidiini, Kaminski et al (2020) found diagnostic characters in the coxite configuration (ovipositor) at the generic level while morphology of genital tubes seems to be stable across the tribe.…”
Section: Discussionmentioning
confidence: 87%
“…Terminology and ratios of female genitalia are those proposed by Tschinkel & Doyen (1980) and Doyen (1994). Following the suggestion of Kaminski et al (2020) to assess homologies in the morphology of female genitalia, we compared the female genitalia of this new genus with previous studies antennomere 10 broader than long (Figs. 2-3), apical tomentose sensory patches on antennomere 9 in two areas, internal larger than external, on antennomere 10 in a semicircle dorsally continuous, on antennomere 11 on distal half (Fig.…”
Section: Methodsmentioning
confidence: 99%